Morphological Characteristics of the Ancient Armenian Translation of "The Book of Fasting" by Basil of Caesarea - Dilbaryan, Narine (Bulletin of Yerevan University B: Philology, 2021)
The famous collection of speeches, conversations, sermons and interpretations of Basil of Caesarea "The Book of Fasting" was translated into the Ancient Armenian language at the end of the 5th to the 7th century, by translators of the period of the Hellenizing school. The language of the Armenian original is figurative and understandable, there are no newly created artificial structures typical of the Greek language. The translators of The Book of Fasting were fluent in both Ancient Greek and their native language. Studying the grammatical features of the language of the Ancient Armenian text proves that Grecisms, tracings of Greek origin are found in the system of  conjugation, especially in the formation of participles and their individual passive constructions, and the declension system of nouns, adjectives and numerals basically corresponds to the grammatical rules of the Ancient Armenian literary language, tracing of Greek the origins are not significant.
Keywords: Basil of Caesarea; “The Book of Fasting”; ancient Armenian translation; the end of the 5th century and the beginning of the 7th century; classical and postclassical Ancient Armenian language; grecisms; Hellenizing school; morphological characteristics; verbal conjugation system; declension